Marx's Wage Theory in Historical Perspective: Its Origins, Development, and Interpretation - Baragar, Fletcher (Labour / Le Travail, 1999)
The article reviews the book, "Marx's Wage Theory in Historical Perspective: Its Origins, Development, and Interpretation," by Kenneth Lapides.